Analysis of genetic diversity evaluation of Lysiphyllum strychnifolium (Craib) A. Schmitz in Thailand using amplified fragment length polymorphism markers - Tangnak, Narumol; Hongtrakul, Vipa; Keeratinijakal, Vichien (Agriculture and Natural Resources, 2018)
Lysiphyllum strychnifolium (Craib) A. Schmitz, a Leguminosae-Caesalpiniodeae species, is colloquially known in Thai as Ya Nang Daeng. In Thai traditional medicine, the leaves, stems and roots have been used to relieve fever and alcohol toxication. The stem has also been used for anti-HIV-1 integrase, anti-allergy and anti-cancer treatment. Confusion over herbal drugs has arisen from the homonymity and morphological characteristics, which present many similarities within its family. Thus, germplasm collection and genetic diversity analysis are prerequisites for a breeding program. In this study, the amplified fragment length polymorphism (AFLP) marker was used to identify and elucidate the phylogenetic relationships among 98 accessions of Ya Nang Daeng throughout Thailand. Thirteen AFLP primer combinations generated 379 bands, of which 359 were polymorphic. The value of the similarity coefficient varied from 0.52 to 0.93, with a mean of 0.73. A phylogenetic tree was constructed using the unweighted major clusters at a cut-off genetic mean (UPGMA) clustering method. The phylogenetic tree derived from the AFLP data showed that the Ya Nang Daeng accessions could be divided into two clusters. Cluster 1 could be further classified into five subgroups, while a similarity coefficient of 0.23 could be used to separate an outgroup from Ya Nang Daeng. The result of principal coordinate analysis and morphological grouping corresponded to the UPGMA clustering. This study showed that the AFLP technique is a useful tool for estimating DNA polymorphism of the genetic diversity and differentiation of related plants. This genetic information will provide useful information for a breeding program in the future.